18F-FDG PET/CT Demonstrating Chorioadenoma Destruens After Evacuation of Complete Hydatidiform Mole. (October 2017) - Sharma, Punit
Abstract : Abstract: Gestational trophoblastic neoplasias (GTNs) are a group of pregnancy-related neoplasms, which include chorioadenoma destruens (invasive mole), placental site trophoblastic tumor, and choriocarcinoma. Although the role of 18 F-FDG PET/CT is still undefined in GTN, in selected cases, it can have significant impact on patient management. Here, we present the case of a 29-year-old woman with hydatidiform mole suggestive of GTN 3 months after evacuation. 18 F-FDG PET/CT demonstrated chorioadenoma destruens (invasive mole) and ruled out metastasis in this case.